STRESS SUPPORTING FACTORS IN FAMILY THAT CARE FOR PEOPLE WITH INTERFERENCE SOUL (ODGJ) - Tinneke A. Tololiu; Esrom Kanine; Sweetly Mamuko (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: Lack of knowledge about how to care for people with mental disorders makes the family feel depressed during the care process. Objective: To determine the factors that cause stress in ODGJ patients. Method: Population is a family that takes family members with mental disorders to the Mental Polyclinic. This type of research is an observational analytic conducted on 41 respondents. Accidental sampling technique. The measuring instrument used was a questionnaire that had been tested for validity based on Corrected item-total Correlation with alpha Cronbach's variables above 0.60. Results: This study showed no relationship between emotional factors (α = 0.055) and psychological situations (α = 0.118) with stress on the family and there was a relationship of perception (α = 0.044), life experience (α = 0.036) with stress on the family. Conclusions: There is no relationship between emotional factors with stress in families caring for people with mental disorders, there is a relationship between perception factors, life experiences with stress in families caring for people with mental disorders at Prof. Mental Hospital Dr.V.L Ratumbuysang. Suggestions for families are expected to better know and understand how to care for family members with mental disorders and important control to the clinic during illness.